Botriomicosis y strongyloidiasis intestinal en un paciente con infección por HTLV-1. Reporte de un caso. - GUERRA AMAYA, Oscar; SOLARI ZERPA, Lely; GUANIRA CARRANZA, Juan; FERRUFINO LLACH, Juan; ECHEVARRÍA ZARATE, Juan; SEAS RAMOS, Carlos; SAMALVIDES CUBA, Frine; GOTUZZO HERENCIA, Eduardo (Revista Médica Herediana, 2013)
We report a case of botryomycosis and intestinal strongyloidiasis in a patient with HTLV-1 infection. A 23 year-old female patient from Ayacucho, came with a history of a right foot tumor and chronic foot ulcers. The diagnosis of botryomycosis was established by biopsy of the lesion. Because the mild eosinophilia, a microscopic examination of stools was performed and Strongyloides stercoralis rhabditiform larva were found. HTLV-1 ELISA test, performed in order to discharge association with strongyloidiasis, was positive. The clinical presentation, physiopathology of the botryomycosis and the role of the HTLV-1 infection and strongyloidiasis as predisposing factors for botryomycosis are discussed. ( Rev Med Hered 2002; 13: 74-76 ).